Hematotoxicity and nephrotoxicity of long-term administration of Guiera senegalensis (J.F. Gme), Cassia occidentalis (Linn), and Ziziphus mauritiana (Lam) leaves obtained in Birnin Kebbi, Nigeria - Tajudeen O. Yahaya; Esther O. Oladele; MDA Bunza; Abdulrahman B. Yusuf; Abdulrazak Izuafa; Jamilu B. Danjuma; Kelechi Nnochiri (Shahrekord University of Medical Sciences, 2022)
Introduction: Previously, we established the phytochemical composition and short-term administration safety of Guiera senegalensis (sabara), Cassia occidentalis (coffee senna), and Ziziphus mauritiana (jujube) leaves, which are common medicinal plants in Northern Nigeria. In the current study, heavy metal contents and long-term administration effects of the plants' leaf extracts on hematological parameters and the kidneys of albino rats (Rattus norvegicus) were investigated. The heavy metals analyzed were copper, lead, cadmium, nickel, and manganese, while the hematological parameters evaluated were packed cell volume, hemoglobin, red blood cells, white blood cells, lymphocytes, and monocytes. Methods: Twenty-four mixed-sex rats were distributed into four groups of six rats each. Group 1 was made the control, while groups 2, 3, and 4 were administered 1000 mg kg-1 one of the plants extracts for 90 days. Blood and kidney samples were collected across the groups for hematological and histopathological examinations. Results: The heavy metals were present in the extracts within the World Health Organization's acceptable limits. The treated rats were anemic compared to the control. However, on average, only the C. occidentalis group showed significant differences (P<0.05) in hematological parameters. Unlike the control, the kidneys of the rats fed with Z. mauritiana and G. senegalensis showed vacuolation of cytoplasm and tubular degeneration, while the C. occidentalis-fed rats had inflammation and dilated Bowman's capsules. Conclusion: These findings reveal that constant administration of high doses of the extracts for a long time may cause health hazards. People are advised to seek an expert's advice before using the plants.